26.032000

# multiply and simplfy answer, (x²+x+3)(x-3)

mathematics
Mathematics
2 2

multiply and simplfy answer, (x²+x+3)(x-3)

#### Answers

yassautumn

[latex](x^2+x+3)(x-3)= x^3-3x^2+x^2-3x+3x-9= x^3-2x^2-9[/latex]

Mar 26, 2000 01:09

26.032000

mathematics
Mathematics
2 2

multiply and simplfy answer, (x²+x+3)(x-3)

yassautumn

[latex](x^2+x+3)(x-3)= x^3-3x^2+x^2-3x+3x-9= x^3-2x^2-9[/latex]

Mar 26, 2000 01:09

[latex] (x^{2} +x+3)(x-3) x^{3} + x^{2} +3x-3 x^{2} -3x-9 x^{3} -2 x^{2} -9[/latex]